Variabilidade da frequência cardíaca como recurso em fisioterapia: análise de periódicos nacionais - Ferreira, Lucas Lima (2013)
INTRODUCTION: The autonomic nervous system (ANS) could be investigated in a noninvasive way by the heart rate variability analysis (HRV) which has contributed to several health areas such as physiotherapy. OBJECTIVE: To gather information regarding the use of HRV on physiotherapy aims at providing an update of the findings for the area on journals of national circulation. MATERIALS AND METHODS: The journals of national circulation classified as greater than B2 or B2 and with free access and complete texts in some internet sites were searched on 21 area WebQualis resulting on selection of Revista Brasileira de Fisioterapia, Fisioterapia e Pesquisa and Fisioterapia em Movimento using the keywords: autonomic nervous system, sympathetic nervous system, physiotherapy and heart rate variability. RESULTS: The search resulted in 19 articles being 17 clinical trials and two case reports. CONCLUSION: The HRV has been used as a resource of interventions evaluation, as pathological conditions common to clinical practice investigation and to physiological conditions interpretation in physiotherapy. The HRV is principally used to the cardiorespiratory specialty of physiotherapy.